Using extended Bigelow meta-regressions for modelling the effects of temperature, pH, °Brix on the inactivation of heat resistant moulds - Alvarenga, Verônica O. (2018)
The management of Heat Resistant Moulds (HRMs) is considered a great challenge for the juice fruit industry. Neosartorya, Byssochlamys and Talaromyces are three out of the main genera isolated from fruit juices that show great resistance to heat treatments. Several inactivation parameters can be found in the literature, however all of them were carried out in specific food matrices and using diverse inactivation methods. Thus, this meta-analysis study synthesizes the thermal resistance parameters of the three HRMs by adjusting extended Bigelow-based meta-regression models to data on inactivation experiments conducted in different liquid media. The meta-analytical data, extracted from publications between 1969 and 2017, was composed of decimal reduction time (D), inactivation method, temperature of inactivation, pH, °Brix, age of spores, and type of medium (model, juice, concentrates). Pooled D* values (D at 90 °C, pH 3.5 and 12° Brix) were estimated for B. fulva (1.95 min; 95% CI: 1.21–3.11 min), Talaromyces (4.03 min; 95% CI: 3.43–4.74 min), Neosartorya (0.5.35 min; 95% CI: 4.10–7.08 min), and B. nivea (10.32 min; 95% CI: 5.81–18.4 min). It was found that increasing the soluble solids in concentrates tends to cause a lower decrease in the heat resistance of Neosartorya and Talaromyces than increasing the soluble solids in model liquid or juices (p = 0.001; 0.012). In general, the screw-capped tubes and three neck round inactivation methods render higher D* values (p lt 0.05) than the thermal death tubes, the polyethylene bag and the capillary methods. Spores of Talaromyces (overall zpH = 7.56; 95% CI: 5.13–13.5) and Neosartorya (overall zpH = 7.07; 95% CI: 5.04–10.8) appear to be more thermal sensitive to a decrease in medium pH than spores of Byssochlamys (overall zpH = 4.34; 95% CI: 3.20–6.73). The meta-regression models presented in this study can be valuable for estimating pooled inactivation kinetic parameters to be used by the fruit juice industry in the management of thermal processes and in the determination of shelf-life.